The effect of one exhausted exercise session on serum serotonin and prolactin level of men runners - GH Sharifi; AR Babai; A Barkhordari; M Faramarzi; MR Sadeh (طب کار)
Background: Serotonin plays an important role in central fatigue and increases the release of prolactin. To determine the effect of one exhausted endurance exercise session on serotonin serum level of men runners, this study was conducted. Methods: In a laboratory cross-sectional study, blood samples of 14 runners were collected and the level of serum serotonin and prolactin was measured before, immediately after and 10 minutes after exercise using Bruce protocol. Data were analyzed by SPSS 18. Results: According to the results, the average level of serum serotonin before, immediately after and 10 minutes after exercise was 141.26, 241.04 ng/ml and 214.34 and for prolactin was 7.53, 11.83 and 16.84ng/ml, respectively. There was significant difference between both serotonin and prolactin levels and the time of exercise(p<0.05). Conclusion: The present study indicates that one exhausted endurance exercise session can increase blood serum serotonin and prolactin level and fatigue then after. It can be recommended that moderate exercise is useful for ordinary individuals.